Analisis Pengaruh Kinerja Keuangan Daerah terhadap Indeks Pembangunan Manusia (IPM) di Provinsi Nusa Tenggara Barat Tahun 2017 – 2019 - Hanifa Ramadhanti (UNISBA Press, 2022)
Abstract. Financial performance is the level of achievement in the implementation of activities in realizing the goals, objectives, mission and vision of an organization as stated in the formulation of strategic plans (strategic planning). In this case, performance is the output or result of activities or programs that will be or have been achieved in connection with the use of budgets with varying quantity and quality (Regulation of the Minister of Home Affairs Number 13 of 2006). Furthermore, Mardiasmo (2005: 219) defines performance as a comparison of the results achieved with the planning or budget that has been made. Regional financial performance is a parameter in assessing the success or failure of local governments in implementing policies to achieve financial management strategies. The performance measurement system is one of the success factors for local governments in managing good governance. Based on the results and discussion regarding the Analysis of the Influence of Regional Financial Performance on the Human Development Index (IPM) in West Nusa Tenggara Province during the period 2017 – 2019, it can be concluded that the Financial Performance variable has no significant effect on the Human Development Index (IPM) in Nusa Tenggara Province. West in 2017 – 2019 with a coefficient of -9.360005 and a probability value of 0.2494 where every 1% increase in financial performance decreases by 9.3% in the Human Development Index. Abstrak. Kinerja keuangan merupakan tingkat pencapaian dalam pelaksanaan kegiatan dalam mewujudkan sasaran, tujuan, misi dan visi suatu organisasi yang tertuang dalam perumusan rencana strategis (strategic planning). Dalam hal ini kinerja sebagai keluaran atau hasil dari kegiatan atau program yang akan atau telah dicapai sehubungan dengan penggunaan anggaran dengan kuantitas dan kualitas yang tertukar (Peraturan Menteri Dalam Negeri Nomor 13 Tahun 2006). Selanjutnya Mardiasmo (2005 : 219) mendefiniskan kinerja sebagai suatu perbandingan hasil yang dicapai dengan perencanaan atau anggaran yang sudah dibuat. Kinerja keuangan daerah merupakan sebuah parameter dalam menilai berhasil atau tidaknya pemerintah daerah dalam melaksanakan kebijakan untuk mencapai strategi pengelolaan keuangan. Sistem pengukuran kinerja menjadi salah satu faktor keberhasilan pemerintah daerah dalam mengelola pemerintahan yang baik. Berdasarkan hasil dan pembahasan mengenai Analisis Pengarih Kinerja Keuangan Daerah Terhadap Indeks Pembangunan Manusia (IPM) di Provinsi Nusa Tenggara Barat selama periode tahun 2017 – 2019, maka dapat disimpulkan bahwa varibel Kinerja Keuangan tidak berpengaruh signifikan terhadap Indeks Pembangunan Manusia (IPM) di Provinsi Nusa Tenggara Barat pada Tahun 2017 – 2019 dengan koefisien -9.360005 dan nilai probabilitas sebesar 0.2494 dimana setiap kenaikan 1% pada kinerja keuangan menurunkan sebesar 9.3% di Indeks Pembangunan Manusia.